Teaching philosophy in Manila - Ferriols, Roque J. (Budhi: a Journal of Ideas and Culture, 2017)
In this talk, Fr. Roque J. Ferriols, S. J. shares some reflections from his experiences in teaching philosophy for almost fifty years in what he describes as a "small corner of Manila".